Prenatal diagnosis of a rare de novo 1q22‐q25.1 chromosomal deletion syndrome using oligo array CGH. Issue 8 (13th June 2018) - Shariati, Gholamreza; Saberi, Alihossein; Hamid, Mohammad; Galehdari, Hamid; Sedaghat, Alireza; Abdorasuli, Nehzat
Key Clinical Message: We present prenatal diagnosis of a case with a rare de novo interstitial deletion of 1q21‐q25.1 by oligo array CGH and provide detailed information on unbalanced gene content and the breakpoints. The affected fetus was delivered at 37 weeks' gestation with a unique clinical phenotype. Abstract : We present prenatal diagnosis of a case with a rare de novo interstitial deletion of 1q21‐q25.1 by oligo array CGH and provide detailed information on unbalanced gene content and the breakpoints. The affected fetus was delivered at 37 weeks' gestation with a unique clinical phenotype.